Differential expression of tissue factor mRNA and protein expression in murine sepsis - de Waard, Vivian; Hansen, Hjalmar R.; Spronk, Henri H. M.; Timmerman, Janneke J.; Pannekoek, Hans; Florquin, Sandrine; Reitsma, Pieter H.; ten Cate, Hugo (Thrombosis and Haemostasis, 2006)
Tissue factor (TF) is a transmembrane protein, which is essential for initiation of the coagulation cascade. TF has been reported to play an important role in the progression of endotoxin (lipopolysaccharide, LPS)-mediated endotoxemia, being induced in numerous tissues, such as kidney, spleen and lung. We developed and validateda rabbit anti-murine TF peptide antiserum to localize TF protein in a murine sepsis model. TF protein distribution was compared to localization of TF mRNA and fibrin deposits, the ultimate resultant of procoagulant TF activity. Evident LPSmediated TF mRNA induction was observed in the tubular area at the cortico-medullar junction in the kidney, and TF activity was increased after 6 hours of endotoxemia. In the spleen, however, TF mRNA was induced in the interfollicular region upon LPS injection, corresponding to increased TF protein in the same area. The clusters of TF-protein positive cells in the spleen are predominantly granulocytes, but no TF mRNA expression was observed within these cells. Based on these observations and the presence of TF-protein positive granulocytes after splenectomy, we hypothesize that granulocytes take-up TF for transport to other locations in order to initiate fibrin formation or to induce pronflammatory gene expression upon interaction with factor VIIa.
Keywords: Tissue factor; coagulation; sepsis; inflammation; granulocytes